The initiatives of corporate social responsibility as sources of innovations - Navickas, Valentinas; Kontautiene, Rima (Business: Theory and Practice, 2013)
The authors of the article analyze the importance of innovation in gaining competitiveness of company. The innova-tion in business is understood as a broad, continuous, systematic activity that takes place throughout the company. Different types of innovation open new possibilities for companies and contribute to the attainment of competitiveness of companies. By emphasize the importance of creating different types of innovation the article treats of socially responsible initiatives as sources of innovations. The paper deals with the development of socially responsible innovations in Lithuanian companies. Companies in Lithuania innovate in socially responsible way, but for more streamlined development of socially responsible innovations require the better advertence and competence of business representatives. Researched the socially responsible initiatives as sources of different types of innovation, the authors found that an active development of socially responsible initiatives positively influences the creating of business innovations and increases competitiveness of company in the global economy.